(untitled) - Shepherd, Elizabeth (London, 2003)
This book offers practical advice on the use of records staff, media and technology; the manual is designed to be of use to LIS and other organizations wishing to introduce better practice into their routines for managing records and other corporate information resources.
Keywords: Records,Hồ sơ; Management,Quản lý